Is intravoxel incoherent motion magnetic resonance imaging useful for predicting hepatocellular cancer recurrence and invasion of the peritumoral zone after transarterial chemoembolization? - Zhao, Xinyao; Wen, Qingqing; Wang, Junying; Dou, Weiqiang; Zhang, Guowei; Shi, Hao (Journal of cancer research and therapeutics, 2024)
ABSTRACT Purpose: We evaluated the potential role of intravoxel incoherent motion (IVIM) in predicting the therapeutic response and peritumoral invasion in patients with hepatocellular carcinoma (HCC) treated with transarterial chemoembolization (TACE). Materials and Methods: We enrolled 47 patients previously treated with TACE between January 2018 and December 2021. We evaluated the IVIM-derived metrics [apparent diffusion coefficient (ADC), D, D*, f] in the TACE-treated, peritumoral, and parenchymal areas of the liver. Results: The ADCtace and Dtace values (1.13 ± 0.22 × 10−3 m2/s vs 0.95 ± 0.13 × 10−3 mm2/s, 1.28 ± 0.27 × 10−3 mm2/s vs 1.07 ± 0.3 × 10−3 mm2/s, P < 0.05) were higher in the non-progressing groups than in the progressing groups in the TACE-treated areas. Dpt represented the D values in the peritumoral area, which can distinguish between the progressive and non-progressive groups with an AUC of 0.73. The Dstd values, which represent the D values in the peritumoral area normalized by the D values in the liver parenchyma in the non-progressing groups (1.10 ± 0.14 × 10−3 mm2/s), were higher than those of the progressing groups (0.93 ± 0.17 × 10−3 mm2/s). Conclusion: The ADCtace, Dtace, Dpt, and Dstd values reflect the changes in the microstructure of the progressive and non-progressive groups after TACE treatment, showing robust diagnostic performances in predicting the therapeutic response and peritumoral invasion.